2007
DOI: 10.1136/oem.2007.036350
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure levels to wood dust in Italy, 1996–2006

Abstract: This study confirms the previous findings about occupational exposure to wood dust (mainly in wood industry and among woodworking machine operators) and suggests further investigations on other risk sectors (building and repairing of ships and boats). The potential of the occupational exposure database as a source of data for exposure assessment and surveillance is also confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
4
12
1
Order By: Relevance
“…The average wood dust exposure levels in the present study were consistent with the previously reported studies, despite the fact that the sampling methods and sites were different in each study and the wood dust concentrations were not always TWA measurements (Moore et al , 1990; Hamill et al , 1991; Pisaniello et al , 1991; Scheeper et al , 1995; Martin and Zalk, 1998; Teschke et al , 1999; Schlünssen et al , 2001; Rando et al , 2005; Scarselli et al , 2007; Kalliny et al , 2008; Galea et al , 2009; Saejiw et al , 2009; Yamanaka et al , 2009; Kauffer et al , 2010). Wood dust exposure levels may have decreased over recent decades possibly due to the changes in equipment, production methods, and upgrading engineering ventilation system for dust control (Teschke et al , 1999; Galea et al , 2009).…”
Section: Discussionsupporting
confidence: 92%
“…The average wood dust exposure levels in the present study were consistent with the previously reported studies, despite the fact that the sampling methods and sites were different in each study and the wood dust concentrations were not always TWA measurements (Moore et al , 1990; Hamill et al , 1991; Pisaniello et al , 1991; Scheeper et al , 1995; Martin and Zalk, 1998; Teschke et al , 1999; Schlünssen et al , 2001; Rando et al , 2005; Scarselli et al , 2007; Kalliny et al , 2008; Galea et al , 2009; Saejiw et al , 2009; Yamanaka et al , 2009; Kauffer et al , 2010). Wood dust exposure levels may have decreased over recent decades possibly due to the changes in equipment, production methods, and upgrading engineering ventilation system for dust control (Teschke et al , 1999; Galea et al , 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Many citations are 1984 1986 1988 1990 1992 1994 1996 1998 2000 2002 2004 Wood dust expousre (GM) (mg m available which provide details of wood dust exposures in various countries and industries. For example, the overall GM of wood dust exposure data collected in Italy during 1996-2006 was 0.97 mg m À3 (based on over 10 000 measurements) (Scarselli et al, 2008). Mikkelsen et al (2002) also reported similar overall GM for 2362 inhalable wood dust data collected in the Danish furniture industry during 1997-1998.…”
Section: Discussionsupporting
confidence: 48%
“…This difference may be due to the difficulty in determining whether a worker is occupationally exposed to carcinogens, particularly when the exposure level is low (next to the environmental background), the carcinogen is a contained substance, and in presence of mixtures. Some results of the analysis of exposure determinants confirm the findings of a previous study with a similar design, based on occupational exposure to hardwood dust recorded in the SIREP database (Scarselli et al 2008). Particularly, in the southern part of Italy, the mean exposure resulted higher than in the others.…”
Section: Discussionsupporting
confidence: 89%